2011
DOI: 10.1016/j.stem.2010.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Stage-Specific Optimization of Activin/Nodal and BMP Signaling Promotes Cardiac Differentiation of Mouse and Human Pluripotent Stem Cell Lines

Abstract: Efficient differentiation of embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) to a variety of lineages requires step-wise approaches replicating the key commitment stages found during embryonic development. Here we show that expression of PdgfR-a segregates mouse ESC-derived Flk-1 mesoderm into Flk-1 + PdgfR-a + cardiac and Flk-1 + PdgfR-a À hematopoietic subpopulations. By monitoring Flk-1 and PdgfR-a expression, we found that specification of cardiac mesoderm and cardiomyocytes is deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
1,137
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,055 publications
(1,179 citation statements)
references
References 59 publications
40
1,137
1
1
Order By: Relevance
“…Altogether, the three types of cells derived from multipotent cardiovascular progenitors (MCPs) [27,[35][36][37] were massively increased following Eomes expression in DDM, although we cannot rule out that some endothelial and smooth muscle cells could also derive from other progenitors (such as the hemangioblasts [38] that could also be induced following Eomes expression). We and others have recently demonstrated that a combination of monoclonal antibodies (Flk1/Pdgfra) can be used to isolate the earliest Mesp1 expressing MCPs arising during ESC differentiation [16,27]. FACS analysis of ESC 48 h after Eomes overexpression in DDM revealed a significant enrichment for Flk1/ Pdgfra-positive MCPs in Eomes overexpressing cells (Fig 1O, supplementary Fig S2E online), consistent with the increase of Mesp1 expressing MCPs by Eomes in these conditions.…”
Section: Results and Discussion Eomes Promotes Cardiogenesis In Escsupporting
confidence: 75%
“…Altogether, the three types of cells derived from multipotent cardiovascular progenitors (MCPs) [27,[35][36][37] were massively increased following Eomes expression in DDM, although we cannot rule out that some endothelial and smooth muscle cells could also derive from other progenitors (such as the hemangioblasts [38] that could also be induced following Eomes expression). We and others have recently demonstrated that a combination of monoclonal antibodies (Flk1/Pdgfra) can be used to isolate the earliest Mesp1 expressing MCPs arising during ESC differentiation [16,27]. FACS analysis of ESC 48 h after Eomes overexpression in DDM revealed a significant enrichment for Flk1/ Pdgfra-positive MCPs in Eomes overexpressing cells (Fig 1O, supplementary Fig S2E online), consistent with the increase of Mesp1 expressing MCPs by Eomes in these conditions.…”
Section: Results and Discussion Eomes Promotes Cardiogenesis In Escsupporting
confidence: 75%
“…Recent efforts have successfully developed several protocols, by which hESCs can be differentiated into hCMs (Yang et al, 2008;Kattman et al, 2011;Lian et al, 2012;Willems et al, 2012;Zhang et al, 2012). Furthermore, hESC-derived hCMs have been analyzed by microarray and a group of cardiospecific genes were revealed (Beqqali et al, 2006;Cao et al, 2008;Synnergren et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, this chemical alone might be not enough to induce cardiac differentiation from iPSCs. Several studies have shown that various combinations of heart developmentrelated proteins including BMP, activin, Wnt, BMP inhibitor, and Wnt inhibitor induce cardiomyocytes from ESCs [7][8][9][10]. We reported that the context-dependent differential action of BMPs in cardiomyocyte induction is explained by the local action of Noggin and other BMP inhibitors and, accordingly, developed a protocol to induce cardiac differentiation of mouse ESCs through transient administration of Noggin [9].…”
Section: Cardiac Differentiation From Human Ipscsmentioning
confidence: 99%